Cellular phone users’ experiences towards online shopping - Norazah Mohd Suki (v. 2, n. 1, p. pp. 38-45, jan. 2011, 2011)
This study aims to examine cellular phone users’ motivating factors towards online shopping. 100 university students located in Klang Valley, Malaysia were involved as the respondents. They were required to complete a set of questionnaire and had to own a cellular phone in order to be selected as sample in this study. Three from five proposed hypotheses were supported: purchasing information, shopping utilities and service quality. As a result, marketers and retailers should concentrate more on the less important factors in order to encourage and create willingness of the consumers to purchase online. Recommendation for future research is also presented.